Pemanfaatan Limbah Kultur Batch Bioreaktor dan Biochar untuk Meningkatkan Kesuburan Tanah - Agus Halim; Sufriyadi Rahya; Zaitun Zaitun (Institut Pertanian Bogor, 2022)
The purpose of study was to determine the effects of aeration treatment on fish wastewater quality as a liquid organic fertilizer and fish wastewater watering treatment as a liquid organic fertilizer and a biochar application on nutrient content of lettuce and soil chemical properties. This study used a non factorial randomized block design. Treatments combination were watering freshwater frequency (W0: without watering; W1: watering twice a week; and W2: watering 4 times a week) and rice husk biochar dose (B0: without rice husk biochar; B1: 10 g rice husk biochar per polybag; and B2: 20 g rice husk biochar per polybag). The research parameters included: fish culture wastewater quality (pH, Biological Oxygen Demand, Chemical Oxygen Demand, NH3-N, NO3, NO2, Dissolved Oxygen, electrical conductivity, and temperature), plant nutrient content analysis (N, P, and K), and soil chemical analysis (pH, organic C, total N, C/N ratio, available P, and exchangeable K). The results showed that the quality of wastewater after aeration for 4 days met the water criteria to cultivate plants. The nutrient contents in the soil showed criteria for neutral soil pH, very low organic C, very low total N, medium C/N ratio, very high available P, and low exchangeable K. Although the nutrient content in the soil was low, the concentrations of N (1.87-3.08%), P (0.16-0.21%), and K (2.35-3.43%) nutrients in the plant were sufficient for lettuce growth. The combination treatment of watering wastewater 4 times a week and rice husk biochar 20 g per polybag gave better results to increase soil fertility and lettuce plant nutrients. Keywords: liquid waste, plant nutrients, soil amendment, soil chemistry